Avoiding desaturation during endotracheal intubation: is high-flow nasal cannula the answer? - Midega, Thais Dias; Olivato, Guilherme Benfatti; Hohmann, Fabio Barlem; Neto, Ary Serpa (Annals of Translational Medicine, 2019)
Tracheal intubation in critically ill patients is a common procedure in the intensive care unit (ICU), and often is realized in an emergency scenario. Hypoxemia, hypotension, arrhythmia and cardiac arrest are described as severe adverse events related to the procedure, with an incidence around 28% (1,2). Among these intubation-related adverse events, life-threatening hypoxemia and profound desaturation (SpO2 below 80%) are the most frequent ones (3).